Bank liquidity risk determinants analysis: Empirical evidence from Chinese commercial banks. - Li, Xinyi (2019)
Finance is the lifeblood of a country’s the current economy. The core component of the financial system are banks, affecting national economic activities and daily life. The liquidity of commercial banks plays an important role in balancing the safety and profitability of commercial banks. Therefore, it is meaningful to investigating determinants influencing the liquidity, which can better regulate and manage banks. With the rapid development of Internet and the promotion of financial technology commercial banks are facing more and more challenges and fierce competition. The influence of the financial crisis on the banking sector has led international organizations and Chinese regulators to strengthen liquidity regulation. This paper combines literature and empirical analysis together to identify the factors influencing the commercial banks’ liquidity risks. The panel data of 227 active Chinese commercial banks from 2012 to 2018 are selected as the sample of this paper. Selecting two liquidity ratios as independent variables measures the liquidity position of commercial banks according to pervious literatures. On this basis, this paper did an empirical research on the liquidity risk determinants of Chinese banks by applying the fixed effect model. Their results are different due to the different dependent variables, but the results of empirical analysis show that the degree of specialization of banks, the proportion of bank equity, bank profitability, unemployment rate is significant correlated with liquidity. Macro factors have a significant impact on the ratio of liquidity assets to total assets, and the ratio of Loan to deposits is affected by non- interest income ratio.